Studi Literatur tentang Pemanfaatan Learning Management Systems (LMS) untuk Meningkatkan Interaksi serta Kolaborasi Guru dan Siswa - Hastuti, Dwi; Fauziah, Syifah; Edde, Genta Primadana; Wicaksono, Dirgantara (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study aims to examine the use of Learning Management Systems (LMS) in improving the quality of the learning process through a literature review approach. The focus of the study is directed toward analyzing the role of LMS as a digital learning medium that supports the delivery of learning materials, facilitates interaction between educators and students, and enables systematic and structured learning management. This research employed a qualitative literature review method by analyzing relevant national and international journal articles, books, and conference proceedings related to LMS implementation in educational settings. The reviewed literature reveals that LMS plays a significant role in enhancing student engagement, learning flexibility, and independence by providing access to learning resources anytime and anywhere. LMS also supports formative assessment, monitoring of learning progress, and effective communication between teachers and learners. However, several challenges in LMS implementation are identified, including limited digital infrastructure, inadequate technological skills among educators and students, low learning motivation, and resistance to changes in conventional teaching practices. In addition, institutional support and instructional design quality are found to be critical factors influencing the effectiveness of LMS-based learning. The findings of this study provide a comprehensive overview of the potential and limitations of LMS as a digital learning tool in various educational contexts. Therefore, this study recommends strengthening digital infrastructure, improving digital competencies, and developing innovative learning designs to optimize LMS utilization as a strategic instrument for improving the quality of education in the digital era